Pengaruh Pemberian Program Bantuan Sosial Tunai Terhadap Derajat Kualitas Hidup Lanjut Usia - Agustine, Yasmine Fauzia (Paradigma, 2022)
The poverty rate in Indonesia had been decreasing in the past few years. Unfortunately, the poverty rate in Indonesia increased as of March 2020. An aids fund named Bantuan Sosial Tunai was created by the Ministry of Social Affairs in tackling the economic problems in Indonesia. The elderly in Indonesia is one of the priorities to receive the BST aid funds due to their vulnerability. This study aims to identify the socio-economic conditions of the elderly in Kelurahan Wonokromo, determine the effect of the BST program on the quality of life of the elderly in Kelurahan Wonokromo, and identify the manifestation of the influence of the BST program on improving the quality of life of the elderly in Kelurahan Wonokromo. This study uses a correlational quantitative approach with the Biserial Point Correlation test as an analytical tool. Respondents in this study were chosen based on purposive sampling. There were 50 elderly who were included in the MBR list and they were divided into 32 elderly recipients of BST and 18 of them were not recipients of BST. Respondents were asked to fill out the OPQOL Brief-35 instrument by Ann Bowling to find out the effect of the BST program on the quality of life of the elderly. The results show that there is a significance level of 1%, with N = 50 then r table = 0.361, and r count = 0.713. It can be concluded that the proposed hypothesis in this study, stating that there is a relationship between the BST program in the degree of quality of life of the elderly, is accepted. It is proven that there is an influence and a positive relationship between the variable of giving the BST program and the variable of the degree of quality of life of the elderly by 50.8% according to Linear R2 results in this study. Keywords: BST, Quality of Life, Poverty, Elderly, Government